Applied strength of materials - Mott, Robert L. (Englewood Cliffs, N.J. : Prentice Hall, 2009)
Robert L. Mott clearly explains the principles of strength of materials, placing emphasis throughout on applying those principles in mechanical, manufacturing, civil and construction engineering.
Requiring only a prior knowledge of statics, Mott gives the reader a solid background in direct tension and compression, direct shear, bearing stress, torsional shear stress, bending stress, combined stresses and Mohr's circle, columns, pressure vessels, and connections. Also covered are deformations of members due to normal and shearing strains, including thermal deformation and the deflection of beams.
Includes bibliographical references and index.
Keywords: Strength of materials